Codesigning More-than-Human Ecosystems with Social and Environmental Systems: The Gamification of NetWall and BioDiveIn - Marie Davidová; María Claudia Valverde Rojas; Hanane Behnam (Land)
This study explores the integration of gamification into social and environmental systems to enhance urban biodiversity and foster the co-creation of ecosystems. It focuses on two key contributions: the development of tangible ecosystemic interventions, such as habitat extensions and edible landscapes, and the gamification of these interventions to engage communities. The interventions were codesigned using systems-oriented design methods, including gigamapping and prototyping, to produce scalable DIY solutions that empower communities to replicate these practices on their own. Additionally, urban games were created to incentivize participation by rewarding individuals for their contributions to biodiversity restoration.